Educational Technology Competency Framework: Defining a Community of Practice Across Canada - Lyn Sonnenberg; Arif Onan; Douglas Archibald (The Canadian Network for Innovation in Education (CNIE), 2021)
Post-secondary institutions need clarity regarding what their educational technology teams can offer. Educational technology is not simply a hammer that can be quickly utilized, but rather an instrument that needs to be tuned for each unique learning context. Using a modified Delphi approach, we validated an educational technology framework that highlights the necessary capabilities, competencies, and example activities needed in higher education across Canada, which moves away from traditional roles and responsibilities. This framework captures the need for teams to educate, collaborate, design, develop, administer, and lead within their institutions. It also highlights the revealed desire and need to create broader communities of practice and collaborations between various institutions. Educational technology teams themselves, when functioning optimally, will not only transform the academic experience for learners and teaching faculty, but they will ultimately shape the direction of higher education's teaching and learning.